Enhancing Plant Diversity in Secondary Forests - Palma, Ana C.; Goosem, Miriam; Stevenson, Pablo R.; Laurance, Susan G. W. (Frontiers in Forests and Global Change, 2020)
Dispersal, recruitment and establishment limitations are crucial processes shaping forest composition. In secondary forests these mechanisms may operate differently than in mature forests, because young and isolated secondary forests may suffer stronger limitations due to a lack of suitable dispersers and harsh environmental conditions—such as the elevated competition of exotic grasses. To assess establishment limitations in these forests, we undertook transplant experiments involving seeds and seedlings along a chronosequence of secondary forests in tropical Australia. The experiments included six species that varied in seed size (6 to 50 mm in length) and successional status (early to late successional). Seeds of five species were placed in one of three treatments: 1) exposed seeds, 2) fenced seeds and 3) buried seeds, and multiple seedlings of six species were transplanted in block treatments. After 14 - 17 months, seeds from all plant species germinated across all ages of secondary forests. However, in young secondary forest sites (4 - 12 years) fewer germinated seeds survived. The highest survival rates were observed for buried seeds (27.2%) compared to the low survival of exposed seeds (6.0%). Planted seedlings (6 spp) had the greatest overall survival (63.1%) and the highest growth rates in older secondary forests. We found that species identity was important for growth and survival in both experiments, but detected no effect of successional status or seed size. A crucial finding of this study was that the buried seeds of all species germinated and had relatively high survival irrespective of variation in site conditions or successional status, suggesting that seed availability may be a greater barrier to recovery of secondary forests in the region than the establishment limitations imposed by environmental conditions.